The Janitor - Tuviera, Michael (Cinemalaya ., 2014)
In 2011, the bloodiest bank heist in Philippine history occurred at Mabuhay Savings Bank in Laguna, leaving ten employees dead, all ruthlessly executed. The perpetrators escape with an estimated P10 million. The robbery is suspected to have been conducted by professionals, as they executed their plan with military precision. Wearing masks to conceal identities, they disabled the bank's security system and held-up the bank personnel inside. Once they got the cash, a fatal mistake leads to an all-out bloodbath. Pressured by the people to resolve the crime, authorities secretly order Crisanto Espina, an ex-cop, to handle the case. Eager to redeem his name, Crisanto hunts down each suspect. But as he finds each name, he unravels the dirty truth behind his extrajudicial duties